Multilingual repertoires and strategic rapport management: a comparative study of South African and Dutch small business discourse. - Lauriks, Sanne (Rhodes University, Faculty of Humanities, Department of English Language and Linguistics, 2014)
In this era of globalisation and the consequent increase in social, economic and physical mobility, small businesses are transforming into sites of increasing language contact (Harris and Bargiela-Chiappini 2003). This study explores situated language practices within two small multilingual businesses. The first is a bicycle rental and repair shop located in Amsterdam (the Netherlands), which is a city with a dynamic multilingual society. The second is a tyre fitment centre in Grahamstown (South Africa), which is a city characterised by a stable triglossia of English, Xhosa and Afrikaans. Using Linguistic Ethnography (Rampton 2007) as my data collection method, I spent a total of eight weeks in these businesses. For the analysis I draw on Spencer-Oatey's (2000b; 2011) Rapport Management Framework and sociolinguistics of globalisation (Blommaert 2010). This combination allowed me to explore situated language practices in relation to a contemporary context of increased globalisation. The analysis is structured using Spencer-Oatey's (2000b) concept of rapport orientations. The orientations are presented as one of the key factors that influence the choice for a certain strategy. The orientations thus seemed a constructive way of showing how the observed strategies were employed by the participants of this study and what function they fulfilled in a certain context. However, difficulties emerged during the analysis with applying this concept to some of the more elaborate and complex data. As a result my argument developed into two different strands. The first demonstrates how individuals turn to their multilingual repertoires to negotiate agency and power relationships in small business discourse. The analysis reveals that people at times deliberately promote and maintains discordant relations, which can be understood as a rational response to the individual's social and economic context. The second discusses the problems that emerged during my analysis with applying rapport management orientations to my data. I propose theoretical developments, warranted by my data, to create an Enhanced Rapport Management Framework suitable for the analysis of complex small business discourse.
Keywords: Discourse analysis; Business communication -- South Africa; Business communication -- Netherlands; Multilingual communication -- South Africa; Multilingual communication -- Netherlands; Communication in management -- South Africa; Communication in management -- Netherlands; Sociolinguistics -- South Africa; Sociolinguistics -- Netherlands; Language and culture -- South Africa; Language and culture -- Netherlands